Disparity and Theory of Legal Ideals Against the Cancellation of the Adoption of Children in the Study of Decisions in the Indonesian General Courts - Peggy Dian Septi Nur Angraini; Rizka; Aidul Fitriciada Azhari (LEGAL BRIEF, 2022)
Arrangements for cancellation of child adoption have not been regulated such as child adoption. This problem is the judge's consideration of examining, adjudicating, and deciding on the decision to cancel the adoption decision, there is a disparity and the judge's decision to cancel the adoption decision has fulfilled the idee des recht legal certainty, expediency, and justice. The normative juridical research method is qualitative in nature referring to laws and regulations and court decisions as well as norms that live and develop in society. There were disparities in 3 (three) civil cases, the Surabaya District Court Decision Number 155/Pdt.G/2017/PN.Sby, the Kendal District Court Decision Number 7/Pdt.G/2018/PN.Kdl and the Central Java High Court Number 389 /Pdt./2018/PT.SMG, and the Decision of the Sragen District Court Number 7/Pdt.G/2020/PN. Sby and the Sragen District Court Decision Number 7/Pdt.G/2020/PN.Sgn have fulfilled the values ??of certainty, fairness, and usefulness, but the Sragen District Court's decision is still lacking in its usefulness. While the decisions of the Kendal District Court Number 7/Pdt.G/2018/PN.Kdl and the Central Java High Court Number 389/Pdt./2018/PT.SMG did not meet the values ??of certainty, fairness, and expediency. Sby and the Sragen District Court Decision Number 7/Pdt.G/2020/PN.Sgn have fulfilled the values ??of certainty, fairness, and expediency, but the Sragen District Court's decision is still lacking in its usefulness. While the decisions of the Kendal District Court Number 7/Pdt.G/2018/PN.Kdl and the Central Java High Court Number 389/Pdt./2018/PT.SMG did not meet the values ??of certainty, fairness, and expediency